Penguatan Peran Pesantren untuk Membangun Pertahanan Umat Islam Indonesia di Era Society 5.0 - Marzuki Marzuki; Budi Santoso; Muhammad Abdul Ghofur (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
This study aims to analyze the strengthening of the role of Islamic boarding schools (pesantren) to build the defense of Indonesian Muslims in the era of society 5.0. Pesantren which is one of the oldest Islamic educational institutions in Indonesia has several main characteristics such as the existence of cottages, mosques, santri (student), ustaz (teacher), kiai, and the yellow book learning. This research is a qualitative research in the form of library research with content analysis method. Sources of data are in the form of several manuscripts, both books and scientific journal articles containing relevant studies to various efforts to strengthen the role of pesantren in strengthening Indonesian Muslims in the era of society 5.0. Data analysis was carried out interactively. The results of the study indicate that pesantren is Islamic educational institutions that has quite a lot of goals, roles, and functions in the midst of society in line with the goals, roles, and functions of Islamic education. Pesantren is also an Islamic educational institution that plays an important role in strengthening Indonesian Muslims so that they have defense and resilience in facing various changes and dynamics of life in the era of society 5.0. Important aspects built by pesantren for the defense and resilience of Muslims include religious, character, educational, social, and economic aspects. As a leading Islamic educational institution in Indonesia, pesantren must be able to equip every Muslim in the current era of society 5.0 so that they can maintain their identity as Indonesian people who uphold religious values ​​and human values.